Research advances on the functions of probiotic fermented milk in regulating body health - ZHAO Cui-yu; WU Zi-jian; LI Shu-sen; LIU Ju-long; ZHANG Xin-yu; SUN Er-na; WEN Yan (Shipin yu jixie)
Probiotic fermented milk is an important carrier of probiotics. It enhances the nutritional and health properties of fermented milk by improving the balance of host intestinal microflora and promoting the metabolism of beneficial ingredients. This review expounds the auxiliary effects of probiotics fermented milk in improving intestinal function, regulating body immunity, assisting in treating metabolic diseases and improving mental system diseases, etc., in order to provide theoretical support for expanding the application of probiotics fermented milk.